Gintonin-mediated release of astrocytic vascular endothelial growth factor protects cortical astrocytes from hypoxia-induced cell damages - Choi, Sun-Hye; Kim, Hyeon-Joong; Cho, Hee-Jung; Park, Sang-Deuk; Lee, Na-Eun; Hwang, Sung-Hee; Rhim, Hyewon; Kim, Hyoung-Chun; Cho, Ik-Hyun; Nah, Seung-Yeol (Journal of ginseng research, 2019)
Gintonin is a ginseng-derived exogenous ligand of the G protein-coupled lysophosphatidic acid (LPA) receptor. We previously reported that gintonin stimulates gliotransmitter release in primary cortical astrocytes. Astrocytes play key roles in the functions of neurovascular systems. Although vascular endothelial growth factor (VEGF) is known to influence the normal growth and maintenance of cranial blood vessels and the nervous system, there is little information about the effect of gintonin on VEGF regulation in primary astrocytes, under normal and hypoxic conditions. Using primary cortical astrocytes of mice, the effects of gintonin on the release, expression, and distribution of VEGF were examined. We further investigated whether the gintonin-mediated VEGF release protects astrocytes from hypoxia. Gintonin administration stimulated the release and expression of VEGF from astrocytes in a concentration- and time-dependent manner. The gintonin-mediated increase in the release of VEGF was inhibited by the LPA1/3 receptor antagonist, Ki16425; phospholipase C inhibitor, U73122; inositol 1,4,5-triphosphate receptor antagonist, 2-APB; and intracellular Ca2+ chelator, BAPTA. Hypoxia further stimulated astrocytic VEGF release. Gintonin treatment stimulated additional VEGF release and restored cell viability that had decreased due to hypoxia, via the VEGF receptor pathway. Altogether, the regulation of VEGF release and expression and astrocytic protection mediated by gintonin under hypoxia are achieved via the LPA receptor–VEGF signaling pathways. The present study shows that the gintonin-mediated regulation of VEGF in cortical astrocytes might be neuroprotective against hypoxic insults and could explain the molecular basis of the beneficial effects of ginseng on the central nervous system.